(untitled) (TAMADDUN NURI JURNALI, 2024)
The role and characteristics of simultaneous translation (ST) in the general system of translation are very wide, and deeper knowledge and skills are required from simultaneous translator. The translator uses simultaneous interpretation of different types of interpretation, in particular, semantic translation from serial translation and different forms and methods. Translation is also a unique bridge which connects these cultures. Whether it is a written translation or an oral translation, at a certain degree it creates an exchange and acquaintance of cultures. Every language reflects the worldview, psyche and identity of that nation. It gives a heavier task for the translator when performing the translation. Today, simultaneous translation is widely used in meetings of heads of state and international conferences. It is natural that the main topic of such simultaneous translation processes is about politics, the political environment in the neighboring and international arena. In carrying out political translation, an experienced translator always takes into account the hidden ambiguity in the speaker’s speech. This is because in the political context of a country, a word that has a positive meaning often has a negative meaning when it is simultaneously translated into another language. It is no coincidence that "Politics is an art." After all, various political metaphors and euphemisms are often used in politics.